Hibridação, performance e utopia nas canções de rap - Cortez, Marcia Felix da Silva (2010)
The present work has as object of investigation the understanding of rap songs as voco-hybrid musical expressions in the Northeast, bring the dialogue between the African-American oral sources and the Northeast. The result of this meeting is built by the analyses of the eighteen songs from Northeastern, and included groups from the design of the poet zumthoriana voice. The identity mapping of MC/a listener of rap has made it possible to deepen looks that were conducted by hybridization, performance considerations, and utopia and, in turn, subsidized a broad approach on textual complexity of rap songs.